The epistolary politics of Virginia Woolf & Ta-Nehisi Coates. Issue 3 (1st September 2020) - Delsandro, Erica Gene
ABSTRACT: In this essay, Erica Gene Delsandro reads Virginia Woolf's Three Guineas (1938) in tandem with Ta-Nehisi Coates's Between the World and Me (2015), highlighting the political efficacy of epistolary writing and amplifying the openness of the interrogatory practice captured by both authors. Ultimately, Delsandro argues for an affiliative reading posture that constellates writers across gender, race, history, and geography in service of examining pressing political questions, then and now.